The excavation of the Knowes of Quoyscottie, Orkney: a cemetery of the first millenium BC - Hedges, Melia E; Rees, S; Young, A; Lunt, D; Williams, D F; Jones, R (Proceedings of the Society of Antiquaries of Scotland, 1979)
HY 302228. A typical Orcadian barrow cemetery consisting of at least ten small mounds, of which four were excavated. They measured 5m-8.5m in diameter, each with a rough stone kerb, and three had cremation burials in central stone cists. Three stone ard-shares were found on the kerb stones. A flat cremation cemetery of thirty-three burials in small pits clustered on the NE perimeter of Knowe 1; some had been deposited before and during the construction of the mound. A thermoluminescence date from burnt stones within Knowe 1 and four 14C determinations from cremation samples gave results in early 1st millennium BC. AR